Pengaruh Pelatihan Keterampilan Dasar Posyandu Terhadap Pengetahuan : Studi Quasi Eksperimen pada Tenaga Kesehatan di Dinas Kesehatan Kota Medan Tahun 2024 - Kartini, Endang; Wandra, Toni; Hutajulu, Johansen; Nababan, Donal; Tarigan, Frida Lina (Journal of Pharmaceutical and Sciences, 2025)
The role of health workers as supporters and trainers in improving performance, providing motivation for Posyandu cadres to always be involved in all Posyandu activities. The level of knowledge of health workers in assessing basic Posyandu skills will greatly determine the quality of services provided. The formulation of the problem in this study through preliminary research conducted on health workers in 10 health centers in Medan City showed that the average value of their knowledge about Posyandu was 63.5 (target ≥ 70). This study aims to determine the effect of health worker training conducted by the Medan City Health Office. The study was conducted using a quasi-experimental method. The number of research samples was 30 people. The material provided was the latest concept and regulation on the integration of primary services at Posyandu. With interactive lecture training methods, group discussions, role play and field practice. The results showed that the mean pre-test value was 72.52 while the mean post-test value was 92.56, there was an increase in value of 29.81 and after being tested with Wilcoxon the p-value was <0.001. The results show that there is a significant difference in the knowledge of training participants about integrated health posts. Knowledge variables according to age, gender, education, work unit, length of service are not factors that influence the pre-test and post-test scores of health workers. It can be concluded that the training that has been given has increased the knowledge of health workers from the post-test assessment conducted. The results of this study are expected to be a medium for evaluating the implementation of basic competency training for integrated health posts for health workers so that the next training period can provide better results.